Development and Empowerment of 21st Century Learning Resources - Rahmi Pertiwi, Getar; Iskandar (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2023)
Learning resources in the 21st century are characterized by technological sophistication. This research aims to explore the concepts, methods and results of developing and empowering learning resources in the 21st century era. This research method includes literature surveys, case studies and qualitative analysis. Understanding the concept of 21st century learning resources is explored by considering the concept and its relevance in the development of science and technology. The development of learning resources is explained through case studies of the application of electronic and digital-based media in educational contexts. The results of this research include an in-depth understanding of 21st century learning resources which are considered as dynamic entities, utilizing the latest technology to increase learning effectiveness. Development methods that have proven effective involve the integration of print, electronic and multimedia media. Implementation of empowering learning resources shows significant improvements in student engagement, learning motivation, and academic results. This research provides important insights into the need to develop learning resources that are responsive to 21st century needs and the strengthened role of empowerment in improving the quality of education. Practical implications and recommendations for further development are also discussed to support continuous improvement in the use of learning resources in the modern era